Lumbar spine injuries: Primary prevention in amateur and professional golf players - Goebel, D.; Drollinger, F.; Drollinger, A. (Sports Medicine International Open, 2018)
In the sport of golf, there is no standard teaching method or swing technique even though golf is known for overuse injuries. This prospective study was to analyze classic swing kinematics in comparison with the Free-Release® method and to define a physiological golf swing. Two hundred eighty-three players, age 50-59 years, were included in the study. For both swing techniques, examination addressed swing visualization, center of pressure (COP), center of mass (COM), as well as pelvic movement in relationship to different standing widths. The position of the spine was evaluated in the frontal and lateral planes. Using the classic technique, no golfer was able to describe his swing parameters, which would be necessary for visualization and to tolerate physiological range of movement, whereas players using the Free-Release method® were able to provide such a description. COP and COM showed pathological swing mechanics for the classic technique, whereas for the Free-Release method mechanics were physiological. We conclude that to prevent lumbar spine injury, the classic swinging technique, which is characterized by lateral shear forces, static and dynamic pelvic side bending while rotating with high force against the spine, and an unbalanced COM and COP, should be substituted by the Free-Release technique as a new physiological guideline.